Designing retroviral vectors for mosquito transformation - Bennett, Michael L., author; Beaty, Barry J., advisor; Higgs, Stephen, advisor; Olson, Kenneth E., committee member; Carlson, Jonathan, committee member; Akkina, Ramesh K., committee member; Bowen, R. A., committee member (Colorado State University. Libraries, 2000)
The retroviral life cycle involves integration of its genome into that of the host cell, a fact that has been exploited in the development of retroviral vectors and their successful use in mammalian transgenesis. The generation of retroviral vectors pseudotyped with the vesicular stomatitis virus envelope glycoprotein (VSV G) has expanded the host range of this technology to non-mammalian systems, including arthropod species. The focus of this work was to test the hypothesis that VSV G-pseudotyped retroviral vectors could be used to transduce mosquito cells with foreign DNA sequences as an approach to generating a transgenic mosquito. VSV G-pseudotyped retroviral vectors carrying the Photinus pyralis (firefly) luciferase gene were constructed and tested for their ability to mediate foreign gene expression in mosquito cells in vitro and in vivo. Two Aedes (C6/36 and AP-61) and one Anopheles (MOS-55) cell lines were able to be transduced, as indicated by luciferase activities up to 58-fold above background. A total 54 out of 1213 Aedes triseriatus mosquito eggs injected with high-titered virus survived to adulthood. PCR identified retroviral vector integration in 3 mosquitoes, but eggs collected from these failed to hatch and transgenic lines were unable to be established. Successful transformation of mosquito cells in vitro demonstrates that VSV G-pseudotyped retroviral vectors can stably introduce foreign genes, but before this technique can be used to generate a transgenic mosquito the methods to deliver and the design of the retroviral vector need to be optimized. The ability to generate high-level gene expression is an important aspect in the optimization of a retroviral vector for use in mosquito transformation. Although a number of candidate promoters are available, the efficiencies of these transcription initiating sequences have not been rigorously compared in mosquito cell lines. To address this issue, the constitutive expression rates of a series of ten promoter/enhancer elements were tested by transiently expressing luciferase in two Aedes mosquito cell lines. Both cell lines produced similar results; the baculovirus IE-1 promoter plus hr5 enhancer from the Autographa califomica nuclear polyhedrosis virus produced the highest amount of expression, followed in descending order of expression by the Aedes densonucleosis virus p7 and p61 promoters transactivated with the NS1 protein, the Drosophilia melanogaster heat shock 70 protein (hsp70) promoter, the p7 and p61 promoters without the NS1 protein, and the D. melanogaster metallothionein (Mtn) promoter. No expression could be detected from the cytomegalovirus (CMV) immediate early promoter or the long terminal repeat (LTR) promoters from Moloney murine sarcoma virus (MoMSV) and Moloney murine leukemia virus (MoMLV). The ability to detect gene expression via a reporter gene is another important aspect in the optimization of a retroviral vector for use in mosquito transformation. To address this issue, several fusion-genes were constructed from the green fluorescent protein (GFP) from Aequorea victoria, firefly luciferase (Luc) from Photinuspyralis, and hygromycin B phosphotransferase (HygR) from Escherichia coliio combine and take advantage of their distinct properties. The chimeric reporters maintained the functions of the original proteins, although the activity of the Luc gene in each fusion was lowered. These reporter fusion genes will be particularly advantageous in retroviral vectors; the expression of multiple reporters from one promoter conserves the limited coding capacity within the vector and decreases the likelihood of rearrangements stemming from additional promoters in between the LTRs. Antisense-mediated intracellular immunity as a long term control strategy in arthropod-borne disease vectors will be dependent upon the ability of cellular and viral RNA transcripts to interact, a concept which has not been established in mosquito cells. To address this, a dsSIN virus vector expressing the 5' 595 bp of the firefly luciferase gene from the second subgenomic promoter was constructed and used to infect transformed Ae. albopictus cell lines constitutively expressing luciferase activity. The resulting 92-97% decrease in luciferase activity compared to cells infected with dsSIN vectors without the antisense luciferase sequence clearly demonstrates that cellular and viral RNA transcripts can hybridize and result in inhibition of protein synthesis in mosquito cells. The demonstration that VSV G-pseudotyped retroviral vectors can infect and mediate stable expression in mosquito cell lines derived from several different mosquito species suggests that this system has the potential to be successfully used in the generation of transgenic mosquitoes, while the failure to actually produce a transgenic mosquito exposes obstacles that must still be overcome. The analysis of promoter function, the construction of multi-reporter fusion proteins, and the finding that RNA transcripts expressed from a cell's nucleus and an infecting virus can associate and produce interference in mosquito cells address some of the key points important in the design of any mosquito transformation technique.
Keywords: microbiology